THE IMPORTANCE OF THE “GREEN CAMPUS” MODEL IN ENHANCING THE SUSTAINABILITY OF HIGHER EDUCATION INSTITUTIONS - Dilshod Qurbanov (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article analyzes the importance of the “Green Campus” model in ensuring sustainable development in higher education institutions. During the research, the advantages of this model were examined based on environmental, economic, and social aspects. Furthermore, foreign and local experiences were studied, existing problems were identified, and proposals for their elimination were developed. The results show that the green campus model is an important tool for effectively organizing the activities of higher education institutions and developing environmental culture.